TINGKAT PEGETAHUAN ORANG TUA TERHADAP PENGGUNAAN GADGET PADA ANAK PRA SEKOLAH DI KABUPATEN BADUNG - Manuaba, I,B; Asri Dewi, N.S; Artawan, K (Sekolah Tinggi Ilmu Kesehatan KESDAM IX/Udayana, 2021)
Many parents let their children play gadgets for hours on the pretext that their children are not fussy, but in reality parents do not understand that excessive use of gadgets can have a negative impact on children. This study use a descriptive research design. The number of samples is 88 parents with preschool children from 100 population. Sampling use purposive sampling technique and the instrument of this study use an online questionnaire through google form that consist of ten statements. Data analysis use SPSS 2019 for window. It is emphasized that most of people's knowledge about the use of gedget in preschool children in Mambal Badung village is good with a total of 60 people or 68.2%. Most of the parents' knowledge about the use of gedget in preschool children in Mambal Village Badung is good. Recommendations for parents to supervise when children play gadgets.